Sustainable water management for sweetcorn in Senegal - Kaiser Lopez, Pablo (Cranfield University, 2012)
Water consumption is a global concern, especially in the agriculture sector in sub-Saharan countries, where 70% of abstraction is for agricultural use. This study was undertaken to evaluate the role of scientific scheduling in reducing the irrigation water applied to sweetcorn without compromising the quality of the product in semi-arid conditions. The experimental site was located at SCL farm (northwest part of Senegal) (latitude 16.12ºN; longitude 16.24ºW and 7 m above sea level) in sandy soils. Three experimental fields were drip irrigated, and equally fertigated, in locations with varying characteristics: unstructured soil (dunes) (Field A), sediments (Field B) and with high groundwater (Field C). The weekly irrigation schedule was developed according to the measured daily crop evapotranspiration (ETc) and periodic measurements of wetting patterns in each field. The schedule aimed to apply water to match ETc and keep the wetted depth close to the estimated root depth in each field. The water consumption in the farm was reduced by 20% on average (23%, 15% and 39% in fields A, B and C respectively), compared to the previous season’s records. Despite reducing the amount of water, the cob yield and quality were similar to SCL expectations. The Irrigation Water Use Efficiency obtained in fields B and C (2.4 and 3.4 kg/m3) were higher than in the previous season (2.1 kg/m3 on average); although in field A it was lower (1.1 kg/m3) due to its low plant density and low yield due to nematode attack. The application of scientific scheduling has allowed similar yield and quality values to be obtained compared to the previous (roughly similar climatically) season, while reducing the water consumption, improving the water efficiency and resulting in other cost savings in manpower, fertiliser and energy.
Keywords: Sweetcorn; Zea mays; drip irrigation; sandy soil; semi-dry; wetting patterns; irrigation water use efficiency; export quality and yield